Prevalence of depressive symptoms and its related factors among students at Tra Vinh University, Vietnam in 2018 - Nguyen Thi Hong Tuyen; Truong Quang Dat; Huynh Thi Hong Nhung (AIMS Press, 2019)
Objective: The study was conducted to estimate the prevalence of depressive symptoms and its related factors among students at Tra Vinh University, Vietnam. Methods: The instrument used was a questionnaire of socioeconomic-demographic characteristics, educational characteristics, and the self-reported depression scale collected from the Center for Epidemiological Studies-Depression (CES-D) originally published by Radloff in 1977. Scores of 16-21 were considered as mild to moderate symptoms of depression, and scores above 21 were considered as symptoms of major depression. The Chi-square test was performed to compare prevalences. Results: 405 students (with 136 males and 269 females) aged 19 to 27 (the average age was 20.2) were interviewed. The mean score for the CES-D was 15.98, and the overall prevalence of depressive symptoms was 52.3%, including the mild to moderate symptoms of depression (24.2%) and the major depression (20.7%). The prevalence occupied 72.2% among students in poor and near-poor households (aOR = 3.06, 95% CI = 1.38-6.76, p = 0.006). The prevalence also was higher among those who had been drinking alcohol (59.7% with aOR = 2.02, 95% CI = 1.15-3.53, p = 0.014).). Depressive symptoms among first-year students were 39.9%, and 2nd-year students were 42.5% and tended to increase to 4th-year students (47.1%) with the p-value of 0.019. Conclusion: The overall prevalence of depression is relatively high among university students at Tra Vinh University, Vietnam. The prevalencesignificantly associates with characteristics such as household economics, behaviours and number of years studying at university. These results suggest that more attention should be directed to activities to reduce the prevalence of depressive symptoms, especially among students in the final years.